New record of the Gray-capped Cuckoo, Coccyzus lansbergi (Bonaparte, 1850) (Cuculiformes, Cuculidae), on the southwest coast of Panama - Kayra Aguilar-Samaniego; Luis F. De León; Celestino Aguilar (Check List, 2020)
This note presents the first record of Coccyzus lansbergi (Bonaparte, 1850) for the southwest coast of Panama. This new record was made on July 11, 2018, in the rural community of Juan Hombrón, Coclé province, Panama. The species has been previously observed in eastern Panama, but this is the first record for the southwestern region of the country. Our record is at least 142 km southwest of its nearest reports in eastern Panama. Overall, this record indicates that the species is likely a vagrant from its known range, given that no other records have been documented south of Coclé, in Panama. In addition, the increasing number of records from eastern Panama over the last 30 years suggests a recent expansion in the northern range of the species.